2023
DOI: 10.1186/s12884-023-05898-7
|View full text |Cite
|
Sign up to set email alerts
|

System interventions to support rural access to maternity care: an analysis of the rural surgical obstetrical networks program

Jude Kornelsen,
Stephanie Lin,
Kim Williams
et al.

Abstract: Background The Rural Surgical Obstetrical Networks (RSON) project was developed in response to the persistent attrition of rural maternity services across Canada over the past two decades. While other research has demonstrated the adverse health and psychosocial consequences of losing local maternity services, this paper explores the impact of a program designed to increase the sustainability of rural services themselves, through the funding of four “pillars”: increased scope and volume, clinic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The care gaps existing among the underserved and marginalized, including pregnant women who have limited access to rural maternity, have been bridged by telehealth and other digital technologies. 39 , 40 The integration of telehealth into maternal care has yielded a reformation of this subsection of the healthcare industry. Through telehealth, a drastic reduction in adverse intrapartum and postpartum outcomes, which may have been associated with delayed care initiation due to poor access to a caregiving facility, has been witnessed.…”
Section: Bridging Health Disparities: the Role Of Digital Healthmentioning
confidence: 99%
“…The care gaps existing among the underserved and marginalized, including pregnant women who have limited access to rural maternity, have been bridged by telehealth and other digital technologies. 39 , 40 The integration of telehealth into maternal care has yielded a reformation of this subsection of the healthcare industry. Through telehealth, a drastic reduction in adverse intrapartum and postpartum outcomes, which may have been associated with delayed care initiation due to poor access to a caregiving facility, has been witnessed.…”
Section: Bridging Health Disparities: the Role Of Digital Healthmentioning
confidence: 99%
“…In interviews and focus groups of 169 providers who were part of this program, participants reported that expanded maternity care teams led to fewer gaps in coverage and allowed for improved continuity of postpartum care. 10 These rural communities have also connected to BC’s virtual supports, including the Maternity and Babies Advice Line, whereby rural providers can seek consultation from peers with obstetrical expertise. Providers described these virtual supports as critical because they enabled access to specialist or peer advice in real time.…”
mentioning
confidence: 99%
“…Providers described these virtual supports as critical because they enabled access to specialist or peer advice in real time. 10 …”
mentioning
confidence: 99%